Conceptual Metaphors in Political Discourse "Mimpi Prabowo Dan Politik Sepiring MBG": A Cognitive Semantic Analysis - Riandi Marcelino; Retty Isnendes; Mahardhika Zifana (Journal of Pragmatics Research, 2026)
Makanan Bergizi Gratis (MBG) is an Indonesian government program initiated by Prabowo Subianto and has been implemented since January 6, 2025. The implementation of this government program has garnered many diverse comments, both supportive and critical. This controversy was also addressed by the Kompas news media through the use of conceptual metaphors. These metaphors were used to help readers understand abstract concepts described through concrete human experiences of political reality. This research is a descriptive qualitative analysis, which aims to analyse conceptual metaphors based on Lakoff and Johnson's theory and Cruse and Croft's image schema theory in an article titled “Mimpi Prabowo dan Politik Sepiring MBG” published by Kompas on October 31, 2025. The results of the research on the political article found 15 conceptual metaphors with the following distribution: 6 structural metaphors, 3 orientational metaphors, and 6 ontological metaphors. There were 15 image schemas, divided into: 3 force image schemas, 3 container image schemas, 3 unity/multiplicity image schemas, 3 scale image schemas, 1 space image schema, 1 existence image schema, and 1 identity image schema.